The influence of job characteristics toward intention to pursue sales career mediated by feelings - Ab Hamid, Siti Ngayesah; Rosli, Nadzirah; Abdul Hamid, Roshayati; Che Wel, Che Aniza (Frontiers in Psychology, 2022)
The sales profession has suffered from negative perception and misconception. Despite a huge opportunity in this industry, several reasons have been highlighted as deterrents to job applicants from applying for a career in sales including the unethical practices, low prestige, and uncertainty of the job. This study examines the influence of job characteristics and feelings on intention to pursue a sales career among undergraduate and postgraduate students. A cross-sectional study was conducted with 251 questionnaires analyzed using Partial-Least Square-Structural Equation Modeling (PLS-SEM). The findings suggest that job characteristics and feelings have a favorable impact on intention. Job characteristics, on the other hand, influence feelings, and feelings mediate the relationship between job characteristics and intention. This study contributes to the body of knowledge by examining feelings as one of the constructs influencing sales career intention, and provides several implications to employers and business instructors to develop effective strategies to spark student interest in sales-related careers.